2020
DOI: 10.1163/15685411-00003324
|View full text |Cite
|
Sign up to set email alerts
|

Pratylenchus penetrans, a potential risk in glasshouse-grown lettuce: population dynamics and damage threshold

Abstract: Summary The root-lesion nematode, Pratylenchus penetrans, causes growth reduction in glasshouse-grown lettuce and is mainly controlled by chemical soil disinfestation. Integrated management strategies require more knowledge about the population dynamics and damage threshold densities. We monitored the population during 2.5 years in a commercial glasshouse by sampling soil in the same four 1 m2 spots at 0-30 cm and 30-60 cm de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Meloidogyne hapla and Pratylenchus penetrans (Claerbout et al, 2020;Viaene & Abawi, 1996) In conclusion, the Paratylenchus populations discovered by this study in Belgian commercial glasshouses were all found to belong to the same, hitherto undescribed species. This nematode can achieve high population numbers on lettuce, with more than 20,000 nematodes (100 ml soil) −1 during winter and spring, which in some cases can cause reduced lettuce growth.…”
Section: Damage Thresholds For Lettuce Have Been Calculated Only Forsupporting
confidence: 49%
See 1 more Smart Citation
“…Meloidogyne hapla and Pratylenchus penetrans (Claerbout et al, 2020;Viaene & Abawi, 1996) In conclusion, the Paratylenchus populations discovered by this study in Belgian commercial glasshouses were all found to belong to the same, hitherto undescribed species. This nematode can achieve high population numbers on lettuce, with more than 20,000 nematodes (100 ml soil) −1 during winter and spring, which in some cases can cause reduced lettuce growth.…”
Section: Damage Thresholds For Lettuce Have Been Calculated Only Forsupporting
confidence: 49%
“…Damage thresholds for lettuce have been calculated only for Meloidogyne hapla and Pratylenchus penetrans (Claerbout et al, 2020; Viaene & Abawi, 1996) and hitherto never for Paratylenchus spp. Winfield (1985) observed poorly‐grown lettuce plants at a final population density of 1,700 P. nanus (100 ml soil) −1 .…”
Section: Discussionmentioning
confidence: 99%